Agriculture shapes the trophic niche of a bat preying on multiple pest arthropods across Europe: Evidence from DNA metabarcoding. Issue 3 (31st January 2018) - Aizpurua, Ostaizka; Budinski, Ivana; Georgiakakis, Panagiotis; Gopalakrishnan, Shyam; Ibañez, Carlos; Mata, Vanessa; Rebelo, Hugo; Russo, Danilo; Szodoray‐Parádi, Farkas; Zhelyazkova, Violeta; Zrncic, Vida; Gilbert, M. Thomas P.; et al.
Abstract: The interaction between agricultural production and wildlife can shape, and even condition, the functioning of both systems. In this study, we i) explored the degree to which a widespread European bat, namely the common bent‐wing bat Miniopterus schreibersii, consumes crop‐damaging insects at a continental scale, and ii) tested whether its dietary niche is shaped by the extension and type of agricultural fields. We employed a dual‐primer DNA metabarcoding approach to characterize arthropod 16S and COI DNA sequences within bat faecal pellets collected across 16 Southern European localities, to first characterize the bat species' dietary niche, second measure the incidence of agricultural pests across their ranges and third assess whether geographical dietary variation responds to climatic, landscape diversity, agriculture type and vegetation productivity factors. We detected 12 arthropod orders, among which lepidopterans were predominant. We identified >200 species, 44 of which are known to cause agricultural damage. Pest species were detected at all but one sampling site and in 94% of the analysed samples. Furthermore, the dietary diversity of M. schreibersii exhibited a negative linear relation with the area of intensive agricultural fields, thus suggesting crops restrict the dietary niche of bats to prey taxa associated with agricultural production within their foraging range. Overall, our results imply that M. schreibersii might be a valuable asset for biological pest suppression in a variety of agricultural productions and highlight the dynamic interplay between wildlife and agricultural systems.